Optimal design of distributed databases - Ceri, Stefano 1955-; Navathe, Sham; Wiederhold, Gio (1981)
The distributed information systems area has seen a rapid growth in terms of research interest as well as in terms of practical applications in the past three years. Distributed systems are becoming a reality, however truly distributed databases are still rare. For a large organization with a distributed computer network the problem of distributing a database includes determination of; (1) How can the database be split into components to be allocated to distinct sites, and (2) How much of the data should be replicated and how should the replicated fragments be allocated? In this paper we design models for solving both of the above problems.
Keywords: Allocations; Computer Hardware; Computer Programming and Software; Computer Systems; Computer architecture; Computer files; Computer logic; Data bases; Data links; Distributed data processing; Global; Methodology; Models; Networks; Nodes; Optimization; Problem solving; Redundancy; Remote terminals; Replicas; Splitting; Topology; Entwurf; Verteiltes Datenbanksystem